Deviation(s) in Project Life Cycle: Case of Construction Industry - GUÐMUNDSDÓTTİR, Svanborg María; ZAİLSKAİTĖ-JAKŠTĖ, Ligita; MİNELGAİTE, Inga (Zenodo, 2022)
Projects in the construction industry frequently demonstrates substantial deviation across the project life cycle. Construction projects, according to this study’s interview analysis in Iceland, frequently suffer from inadequate project management, lack of scope, poor labor use, clients with insufficient finances, and excessive client intervention. Additionally, wider societal factors such as COVID-2019 can negatively impact deviation and undermine project success. The purpose of this study is to identify the factors, that impact deviation in project management and the phases through which it arises in the project life cycle of the construction industry. The paper presents a case study on project management deviation across the project life cycle based on the Icelandic construction industry. The research results identified that project deviation is primarily caused by four factors: 1) clients' ambiguous requirements; a lack of planning, which results in an extended execution phase, often at great expense; 2) Icelandic cultural attitudes; 3) a lack of standardization in project manager operations; and 4) unpredictable external factors that cannot be controlled. In this study revealed project management deviation reasons in relation to project life cycle phases in the Icelandic construction sector. The elimination of deviation factors can help project managers to successfully manage project implementation and ensure successful project life cycle implementation in the construction industry.